If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + 2) + -1(3x + -6) = 0 Reorder the terms: (2 + 4x) + -1(3x + -6) = 0 Remove parenthesis around (2 + 4x) 2 + 4x + -1(3x + -6) = 0 Reorder the terms: 2 + 4x + -1(-6 + 3x) = 0 2 + 4x + (-6 * -1 + 3x * -1) = 0 2 + 4x + (6 + -3x) = 0 Reorder the terms: 2 + 6 + 4x + -3x = 0 Combine like terms: 2 + 6 = 8 8 + 4x + -3x = 0 Combine like terms: 4x + -3x = 1x 8 + 1x = 0 Solving 8 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = 0 + -8 1x = 0 + -8 Combine like terms: 0 + -8 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| -5(.2+.2y)=-2 | | -8(5+b)-1=-89 | | 124=7x+3(x+8) | | 2(x+8)=9x-6 | | 6x-2y=48 | | (2+x)(x-3)=24 | | 5xn-3=12 | | 7x-22=6x-22 | | 10x-2y=2 | | 20-4a+4a+4a+7=48 | | -6(1+8k)=-102 | | 9.6=1.6 | | 6b+4=12 | | 8y-3y=75 | | (7y+6)-(5+6y)=5 | | (3)(2x)(x)=36 | | 3x-2(5(6)+14)=-14 | | 4.1x-4=3.1x | | 3x-9(-4)=36 | | 6(-3x+6)=-180 | | 3x-2(5(6)+14)= | | -12-3y-3y=12 | | x^2+10=18x-12 | | 3(x+6)+8=5x-6 | | (35)=3x+2 | | 3t=37 | | B=r+50 | | 6x-5+4x-4=x | | 2x+67=-8x+107 | | 8b(b+3)= | | 15+3x=-2x-30 | | 6(a+3)-10=-2a+7 |